Evaluation of Hot Pepper Varieties through Farmer’s Participatory Selection at Teppi area, Southwestern Ethiopia - Sora, Shamil Alo; Getahun, Betelhem (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Three hot pepper varieties were evaluated in single plot in 2022/23 main cropping season. Farmers’ evaluation was made at two different stages of the crop, namely at vegetative and at maturity using both direct-matrix and pair-wise ranking methods of selection scheme. Farmers’ set; green pod yield, disease tolerance, pod color and size as selection criteria to evaluate and identify their preferred varieties. The results of analysis of variance indicated the existence of highly significant differences among varieties for all traits measured at 5% probability level. The highest mean green pod yield was obtained from the variety Melka Awaze (11.39 t/ha) and Melka Zala (8.39 t/ha). Likewise, these two varieties were identified as farmers preferred varieties from both pair-wise and direct matrix ranking evaluations. Thus, the varieties Melka Awaze and Melka Zala were chosen for their performance in the field and from farmers' evaluation perspective. Moreover, this study indicated participatory varietal selection is a viable method to gain greater insight into farmers’ perceptions, preferences, merits and shortcomings of hot pepper varieties. Therefore, based on the results of this study, Melka Awaze and Melka Zala varieties are recommended for multiplication and distribution to farmers in the area.